An expression atlas of variant ionotropic glutamate receptors identifies a molecular basis of carbonation sensing - Juan Antonio Sánchez-Alcañiz (Nature Portfolio, 2018)
Little is known about the role of variant ionotropic glutamate receptors (IRs) in insect taste. Here the authors characterise the expression pattern of IRs in the Drosophila gustatory system and highlight the role of one receptor, IR56d, in the detection of carbonation